Ethnography, ethics and ownership of data. (March 2020) - Russell, Lisa; Barley, Ruth
Establishing trust and obtaining informed consent with participants is reliant upon on a process whereby unequally positioned agents constantly re-negotiate (mis)trust and consent during ethnographic encounters. All research has been increasingly subject to an intensification in ethical regulation, within a context whereby Eurocentric norms and ethical guidelines arguably diminish individual accountability under the guise of quasi-contractual relationships. This phenomenon has particular implications for ethnography and its management of ethics, given its intimate, longitudinal and receptive nature. Two expert ethnographers working with children and young people draw upon their work to reveal how issues of informed consent and data ownership can shift and be a source of tension and unequal power dynamics. The ethnographer requires autonomy while managing ethics soundly in situ to work within the messiness and unpredictability of participants' everyday lives.